2019
DOI: 10.1037/mgr0000081
|View full text |Cite
|
Sign up to set email alerts
|

Before you send that: Comparing the outcomes of face-to-face and cyber incivility.

Abstract: The increasing use of information and communication technologies has allowed for a new type incivility known as cyber incivility. This study compared the correlations of face-to-face and cyber incivility with job satisfaction, burnout, and turnover intentions. Data were collected from 231 participants who completed an online survey asking about the aforementioned work outcomes and face-to-face and cyber incivility. Results indicated that face-to-face and cyber incivility were both significantly correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
(234 reference statements)
1
7
0
Order By: Relevance
“…A notable pattern in our findings in this regard was that while face-to-face incivility showed robust daily effects in the outcomes studied, cyber incivility had much less apparent effects (it only exhibited an indirect effect on daily emotional exhaustion via sadness). The findings we observe in this respect are consistent with those reported in Heischman et al's (2019) survey study, which found stronger associations between face-to-face incivility and detrimental outcomes, including burnout and turnover intention, in comparison to cyber incivility. Our findings contribute beyond those already reported by suggesting that one reason why exposure to cyber incivility may not have as large an impact on such outcomes is that it does not evoke an intense emotional response.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A notable pattern in our findings in this regard was that while face-to-face incivility showed robust daily effects in the outcomes studied, cyber incivility had much less apparent effects (it only exhibited an indirect effect on daily emotional exhaustion via sadness). The findings we observe in this respect are consistent with those reported in Heischman et al's (2019) survey study, which found stronger associations between face-to-face incivility and detrimental outcomes, including burnout and turnover intention, in comparison to cyber incivility. Our findings contribute beyond those already reported by suggesting that one reason why exposure to cyber incivility may not have as large an impact on such outcomes is that it does not evoke an intense emotional response.…”
Section: Discussionsupporting
confidence: 92%
“…While studies of each type of incivility independently have indicated both to Daily Effects of Incivility via Discrete Emotions 16 cause important impairments to employees (e.g., Zhou et al, 2015), emotions have only been studied as antecedents of cyber mistreatment (e.g., Vranjes et al, 2018), meaning that the potential for emotions to explain the detrimental effects of cyber incivility was unknown. More generally, our understanding of their relative effects has been hampered by the fact that the few previous studies that include both types of incivility suffer from methodological issues that limit the confidence of conclusions in application to day-to-day workplace incivility (e.g., use of student samples: McCarthy et al, 2020;Scisco et al, 2019; reliance on retrospective reports: Heischman et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the existing work have investigated how cyber incivility results to psychological distress, negative affect and intention to quit (Heischman et al, 2019;Park et al, 2018;Williams and Loughlin, 2015); revenge (Tripathi and Lim, 2014); lower work engagement, motivation and energy (Giumetti et al, 2013); job satisfaction and organizational commitment (Lim and Teo, 2009;Ballon, 2018;Park et al, 2018). The mechanical stages process by which knowledge hoarding behavior emerge as a result of organizational (Zhao and Xia, 2017), situational (Jain, 2012) and personal (Anaza and Nowlin, 2017) factors have been conceptually explored.…”
mentioning
confidence: 99%
“…Online communication has become more prominent in universities and clinical settings [ 11 , 12 , 16 , 34 , 49 , 50 ], due to its advantages of flexibility of location and time [ 10 , 51 ], and its use is especially important, given the social distancing measures brought about by the COVID-19 pandemic [ 16 ]. Cyberincivility can have a profound negative psychosocial impact on users and their community [ 52 , 53 ], resulting in emotional distress (e.g., cynicism, fear, lowered self-confidence, and burnout), social isolation, distrust and avoidance, and turnover intentions [ 34 , 54 , 55 ]. The creation and maintenance of a safe, supportive, and civil learning environment is important for both educators and their students [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%